2015
DOI: 10.1007/s00213-015-4041-8
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical characterization of toluene as a non-classical hallucinogen drug in rats: participation of 5-HT, dopamine and glutamate systems

Abstract: Toluene stimulates 5HT2A and 5HT2C receptors, and increases 5-HT and DA levels. These actions are similar to those produced by ketamine and involve activation of a complex neurotransmitter network that includes NMDA receptor antagonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 66 publications
0
2
1
Order By: Relevance
“…S6A). After systemic ketamine injection, consistent with previous reports (69)(70)(71), there was a marked increase in the 5-HT signal in control mice (fig. S6, B to D).…”
Section: Local Knockout Of Nr1 In Lhb Reduces Systemic Ketamine-induc...supporting
confidence: 92%
“…S6A). After systemic ketamine injection, consistent with previous reports (69)(70)(71), there was a marked increase in the 5-HT signal in control mice (fig. S6, B to D).…”
Section: Local Knockout Of Nr1 In Lhb Reduces Systemic Ketamine-induc...supporting
confidence: 92%
“…A decrease in sexual motivation could be related to a deficiency in dopamine, as this neurotransmitter is involved in the processing of the appetitive, motivational and rewarding aspects of sexual activity (Damsma, Pfaus, Wenkstern, Phillips, & Fibiger, ; Everitt, ; Fiorino, Coury, & Phillips, ; López & Ettenberg, ; Wenkstern, Pfaus, & Fibiger, ). In our work, this does not seem to be the case because concentrations of toluene similar to ours increase dopamine content (Rivera‐García, López‐Rubalcava, & Cruz, ) and release (Koga, Higashi, Kawahara, & Ohsumi, ; Stengård, Höglund, & Ungerstedt, ) in the mesolimbic system of rats. The idea that sexual motivation was not compromised in our experimental subjects is reinforced by the fact that toluene‐treated sexually experienced animals exhibited a high number of mounts prior to the first intromission, evidencing their interest in the sexual interaction, even in the absence of the penile sensory stimulation from an intromission (Carro‐Juárez, Cervantes, Cervantes‐Méndez, & Rodríguez‐Manzo, ).…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, considering the complexity of the epilepsy, further efforts are needed to try to understand why could certain odors and, sometimes, the same odor (usually in different concentrations) can both precipitate or arrest seizures [29,112,113], in especial those with origin in the temporal lobe. In that context, preliminary data from our group indicated that 2,5-dihydro-2,4,5-trimethylthiazoline (TMT), a biological relevance odor, "predator odor" reduced both the behavioral and the EEGraphic seizure activities [114,115], in amygdala rapid kindling [116], a model of TLE. With the identification of some of the molecular effects of TOL, various research groups investigated the metabolic and neurochemical changes associated with TOL exposure [76] as also shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%